The Influence of Gamification Media Usage on the Enhancement of Cognitive Abilities in Children Aged 5-6 Years - Aisya Miftahul Jannah; Aprilia Sugiarti (IRDH International Journal of Social Sciences & Humanities, 2025)
This research was conducted to systematically describe the influence of gamification media in learning at TK Putra Harapan Surabaya on logical thinking and problem-solving in enhancing cognitive abilities, particularly in children aged 5-6 years. The research method used is quantitative descriptive, where this study employs a pre-test and post-test to compare the presence of variables in different samples. The data collection technique in this research utilizes observation, specifically direct observation at TK Putra Harapan of children engaged in learning in group B. After the data is collected, data analysis techniques will be performed by measuring indicators of objectivity level, validity level, and reliability level. Subsequently, these indicators will be tested using statistical testing tools such as the T-test or chi-square test.